Application of Inter-Organizational Communication for Collaboration (Descriptive Study Between UPT BP2MI East Java and P3MI in East Java) - Kriyantono, Rachmat; Sekartaji, Dewi (Technium Social Sciences Journal, 2022)
The increase in the number of complaints by Indonesian migrant workers (PMI) from 2017 to 2019 raises big questions as to why this case happened, especially in the province of East Java with the fourth largest number of complaints in Indonesia. The function of UPT BP2MI in East Java and P3MI in East Java is questioned, how big is their role in protecting PMI, including how they collaborate to achieve this.This research will use the constructivist paradigmwith the IOC and Collaboration approach which aims todescribe how the application of communication between UPT BP2MI East Java and P3MI in East Java to collaborate with each other in protecting PMI. Informants in this study were employees of UPT BP2MI East Java and representatives of P3MI East Java which consisted of 4 companies that the researchers interviewed. Researchers can build the proposition thatobstacles come from the center, not UPT BP2MI East Java. In addition, researchers can conclude that communication between UPT BP2MI East Java and P3MI East Java is going well although there are still shortcomings. Its good application also makes collaboration elements able to be achieved well.